The Students’ Mathematics Learning Difficulties Analysis - Wahyu Purwaningsih; Haryanto Haryanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
This study aims to describe, interpret, and analyze the PGSD UPY students’ difficulties in learning mathematics 2. The research type is a descriptive qualitative research. The research subjects are students and a mathematics lecturer of PGSD UPY. The data were gathered through interviews, observations, documentations, and tests. The data validity test was done by using triangulation of sources and techniques. Proprietary interactive analysis models (Miles, Huberman, & Saldana, 2014) were used to analyzed the data. The results show that there are some difficulties experienced by students in learning numberic system especially for fractions. The pretest and post test results show that  A1 and A2 students get low average score on fractions materials. The average score of the pretest for A1 is 66.11 while A2 is 62.35. The average core of the posttest for A1 is 67.22, while A2 is 63.52.